Study of the Spectral Energy Distribution Model of the Protoplanetary Disk Geometric around the Brown Dwarf CFHT-BD-Tau 4 - Taha, Anas S.; Alkotbe, Bashar; Ali, Arshed (Iraqi Journal of Science, 2024)
The accretion circumstellar disk of young stars and the Brown dwarf plays an essential role in the formation and evaluation of the planet. Our main work in this paper is to investigate the geometrical shape model for the protoplanetary disk around one of the Brown Dwarfs. The photometric measurements for the brown dwarf CFHT-BD-Tau 4 were extracted from the Vizier archive. We used a numerical simulation to build a model of the spectral energy distribution of our target CFHT-BD-Tau 4. The spectral energy distribution model was fitted with observational data for the brown dwarf CFHT-BD-Tau 4. A transitional disk has been assumed around CFHT-BD-Tau 4. We obtained physical properties of the two disks and the size of the gap between them by fitting the SED. The gap in the protoplanetary disk proves that a planet formation process occurred around the Brown dwarf.